G160(P) Prepubertal vaginal bleeding – an unusual cause. (24th May 2017) - Broomfield, R; Pryce, R
Abstract : Aim: To present an unusual case of prepubertal bleeding and raise awareness of a possible differential diagnosis. Up until menarche vaginal bleeding after the first month of life is always abnormal and therefore it is justified to investigate in order to determine a cause. Methods: Case Presentation: A five year old girl presented to the CAU unit with the 7th presentation of vaginal bleeding since the age of two. She had been previously investigated with numerous blood tests including hormonal profiles, several pelvic ultrasound scans, and an examination under anaesthetic which were all normal. There was no evidence of precocious puberty. On her most recent past admission, she underwent a further examination under anaesthetic which included a colposcopy. A cervical ectropion that bled on contact, was treated with silver nitrate. Due to her multiple presentations and the nature of her complaint the case had been discussed with police and social services. Sexual abuse and fabricated illness were considered in the differential diagnosis. No evidence of abuse was found. Results: The most recent presentation was her most significant episode of vaginal bleeding. Previous episodes had not led to any haemodynamic compromise or appreciable fall in haemoglobin. However on the last occasion, after a week of ongoing bleeding her haemoglobin levels had halved. She received two blood transfusions and was subsequently transferred to a specialist centre with a paediatric surgical and gynaecological expertise for ongoing management. She underwent an abdominal/pelvic MRI which was normal, however on examination under anaesthetic there was an arterio-venous (AV) malformation noted on her cervix. This was cauterised at the time, resulting in termination of her vaginal bleeding. Conclusion: It is important to fully investigate any prepubertal girl presenting with vaginal bleeding – we would suggest this includes a visual examination and a colposcopy if the cause of bleeding remains unclear. Expert opinion should be sort when initial investigations are inconclusive. It is important to consider common causes such as vaginitis but also rarer causes. AV malfomations of the cervix are extremely rare and this is the first paediatric presentation that we are aware of.